2023
DOI: 10.1097/nhh.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Resilience and Caregiver Burden Among Home Caregivers of COVID-19 Patients

Abstract: This study examined caregiver burden among home caregivers of COVID-19 patients and its relationship to resilience. This cross-sectional correlational study was conducted in Mashhad, Iran, in 2020. The sample consisted of 220 family caregivers of COVID-19 patients. The data collection tools included: demographic characteristics, Novak and Guest Caregiver Burden Inventory, and Connor-Davidson Resilience Scale. Data were analyzed with descriptive statistics and correlation test in SPSS v25. The mean score of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…The objective of this study was to examine the predictors of care burden among caregivers of patients with COVID‐19. The findings of the study revealed that a majority of caregivers experienced a significant care burden, which aligns with the results reported by Mirzaei et al ( 2020 ), Cohen, Kunicki, et al ( 2021 ) and Manzari et al ( 2023 ). However, contrasting findings were reported in some studies where caregivers reported a moderate care burden (Akkuş et al, 2022 ; Ebrahimi et al, 2022 ; Russell et al, 2020 ; Sayadi & Masoumi Fard, 2022 ; Sheikhbardsiri et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…The objective of this study was to examine the predictors of care burden among caregivers of patients with COVID‐19. The findings of the study revealed that a majority of caregivers experienced a significant care burden, which aligns with the results reported by Mirzaei et al ( 2020 ), Cohen, Kunicki, et al ( 2021 ) and Manzari et al ( 2023 ). However, contrasting findings were reported in some studies where caregivers reported a moderate care burden (Akkuş et al, 2022 ; Ebrahimi et al, 2022 ; Russell et al, 2020 ; Sayadi & Masoumi Fard, 2022 ; Sheikhbardsiri et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Caregivers have to be highly adaptable and flexible, and these skills may have benefited them during the pandemic. Caregivers with higher resilience experienced less burden during the pandemic (Palacio et al, 2020;Manzari et al, 2023). Additionally, prior research shows individuals experiencing loneliness who use positive coping mechanisms are able to reduce their feelings of loneliness (Fluharty et al, 2021).…”
Section: Discussionmentioning
confidence: 99%